The day that shook America : a concise history of 9/11 - Walker, J. Samuel (Book collections on Project MUSE., 2021)
"The 9/11 disaster is one of the most important stories in all of American history, and The Day That Shook America tells the whole story, from causes to consequences, in a concise and compelling way. Covering both government policy and human impact, and drawing on extensive oral histories, J. Samuel Walker's history of 9/11 provides a comprehensive yet succinct account of this tragedy-including the policy mistakes and misplaced priorities that resulted in the Clinton and Bush administrations failing to take effective action against al Qaeda, how the four al Qaeda hijacking teams carried out their plan, the responses by federal agencies to the plot, the "hell on earth" it created for the people trapped in the buildings, and the response by the Bush administration. Looking back twenty years later, The Day That Shook America is a timely and valuable guide to the defining moment of the United States in the twenty-first century"--